2016
DOI: 10.1111/tmi.12741
|View full text |Cite
|
Sign up to set email alerts
|

Intensive adherence counselling for HIV‐infected individuals failing second‐line antiretroviral therapy in Johannesburg, South Africa

Abstract: Most (64%) second-line treatment failure in this clinic is related to adherence and can be overcome with careful adherence support. Controlled interventions are needed to determine what the optimal approach is to improving second-line outcomes and reducing the need for third-line ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 21 publications
(24 reference statements)
11
40
2
Order By: Relevance
“…Further, our results show it is difficult to get patients to return to care and to ensure they are retested within the 3 month period to determine EAC success. While we have previously found such a targeted approach can be successful for patients with elevated viral loads [37], without a randomised design it has been hard to argue these associations are causal and these findings suggest they may not be. We do note that delays in viral load testing may have an influence on resuppression given that resistance can develop quickly with NNRTI-based regimens like those being used in South Africa.…”
Section: Discussionmentioning
confidence: 88%
“…Further, our results show it is difficult to get patients to return to care and to ensure they are retested within the 3 month period to determine EAC success. While we have previously found such a targeted approach can be successful for patients with elevated viral loads [37], without a randomised design it has been hard to argue these associations are causal and these findings suggest they may not be. We do note that delays in viral load testing may have an influence on resuppression given that resistance can develop quickly with NNRTI-based regimens like those being used in South Africa.…”
Section: Discussionmentioning
confidence: 88%
“…This evidence provides an opportunity for engaging patients from treatment initiation by providing additional support and counselling to ensure that they remain engaged throughout their treatment span. [35] Support and counselling benefits have been reported in firstline treatment cohorts where similar retention-in-care patterns were identified. [35,36] Mberi et al [36] described a group receiving care from 2002 to 2012 at a high-volume SA ART clinic.…”
Section: Researchmentioning
confidence: 82%
“…[35] Support and counselling benefits have been reported in firstline treatment cohorts where similar retention-in-care patterns were identified. [35,36] Mberi et al [36] described a group receiving care from 2002 to 2012 at a high-volume SA ART clinic. They reported 40% of the patients being LTFU within 12 months of starting ART, a slight subsequent decrease in retention, a sharp decline from year 5, and plateauing at year 8.…”
Section: Researchmentioning
confidence: 82%
“…In other words, without DRT, more than 60% of patients with VF included would have been unnecessarily switched to third‐line ART. Recent studies also reported a significant proportion of second‐line failure without major resistance to the current regimen and poor adherence was indicated as a major factor underlying VF .…”
Section: Discussionmentioning
confidence: 99%